Study on the effect of nigella sat/va oil towards oxidized low density lipoprotein uptake by primary human monocytes/macrophages - Mat, Mahaya Che (2011)
Monocytes and lipid-laden macrophages have been reported to play various roles in atherogenesis. Nigel/a saliva, a natural product with various medical benefits was used in the study to evaluate its antilipid effects. The focus was to elucidate the effects of Nigel/a sativa oil on the progression of monocyte-derived macrophages growth in vivo via the effect on uptake of oxidized LDL. Human monocytes were isolated using magnetic beads Dynabead MyPure Negative Isolation Kit and identified with Wright staining. The cells were grown at 37°C and 5% co2 saturation for 5 days until 90% confluence prior to treatment. The cells were then plated in 24-well plate and washed before treated with oxLDL (10 μg/ml) or combination of ox-LDL (10 μg/ml) and (72 μg/ml) Nigella saliva oil. The growth progression was monitored every 24 hours for 3 days using phase-contrast microscopy. The oil red 0 staining was used to visualize intracellular lipid deposition. Detection of surface marker antigen CD 11 b was done with flow cytometry analysis to compare monocyte-to-macrophage differentiation in the cells supplemented with oxidized LDL alone (20 μg/ml) and in combination of oxidized LDL (20 μg/ml) and Nigel/a saliva oil (72 μg/ml). It was found Nigel/a saliva oil caused significant growth reduction on monocyte and macrophage growth especially 24 to 48 hours after treatment {p<0.001). The mean sizes were significantly different between treatment with oxidized LDL alone and combination treatment for both monocytes and macrophages (p<0.001 ). The delayed growth pattern was more in macrophage groups compared to monocytes in the timeline studied. There were less oil red 0 staining in cells treated with combination of oxLDL and Nigella saliva compared to those treated with oxLDL alone. Flow cytometry analysis showed reduced expression of mean fluorescence intensity in cells treated with combination of 60% Nigella sativa oil and oxidized LDL compared to cells supplemented with native LDL and oxidized LDL alone. These preliminary findings indicate the progression of macrophage to foam cells could possibly be controlled with Nige/la sativa oil treatment at specific level.